Dermatology: how to manage psoriasis and recognize differences in pathophysiology and presentation in patients with skin of colour - Yuliya Lytvyn; Muskaan Sachdeva; Asfandyar Mufti; Jensen Yeung (BioExcel Publishing Ltd, 2022)
Psoriasis is a chronic inflammatory skin condition that affects diverse ethnic groups with a wide spectrum of skin colours. There are significant differences in how psoriasis presents and impacts the quality of life in non-White individuals. Genetic variations as well as cultural and socioeconomic factors all play a role in such differences and have important implications for the management of psoriasis in skin of colour. Despite these differences, the current psoriasis management is similar across different ethnic backgrounds and is mainly guided by factors such as disease severity, medical comorbidities and patient preferences. This is largely due to the lack of sufficient evidence for psoriasis treatment tailored for patients with skin of colour as most clinical trials are composed of mainly White individuals. Therefore, the focus of this article is to review the current evidence on how epidemiology, clinical presentation and genetic differences in patients with skin of colour with psoriasis may impact treatment strategies. Additionally, pharmacological therapies available to date in these diverse patient cohorts are summarized in this article. The limited data published on this topic reveal a significant need for more investigations with the ultimate goal of incorporating recommendations for patients with skin of colour into the current guidelines for psoriasis treatment. Moreover, awareness of differences in psoriasis presentation amongst individuals with skin of colour may support patients to seek medical care sooner, which could result in earlier diagnosis and lead to improved patient outcomes.